Sexual violence and associated factors among women of reproductive age in Rwanda: a 2020 nationwide cross-sectional survey - Lilian Nuwabaine; Joseph Kawuki; Earnest Amwiine; John Baptist Asiimwe; Quraish Sserwanja; Ghislaine Gatasi; Elorm Donkor; Humphrey Atwijukiire (BMC, 2023)
Abstract Background Sexual violence against women is a global public health issue with both short- and long-term effects on the physical and mental health of women. This study aimed to determine the prevalence of sexual violence and its associated factors among women of reproductive age in Rwanda. Methods We used secondary data from the 2020 Rwanda Demographic and Health Survey of 1,700 participants, who were selected using multistage stratified sampling. Multivariable logistic regression was conducted to explore factors associated with sexual violence using SPSS (version 25). Results Of the 1,700 women of reproductive age, 12.4% (95%CI: 11.0-14.1) had experienced sexual violence. Justified beating (AOR = 1.34, 95%CI: 1.16-1.65), not having health insurance (AOR = 1.46, 95%CI: 1.26-2.40), not being involved in healthcare decision-making (AOR = 1.64, 95%CI: 1.99-2.70), having a husband/partner with primary (AOR = 1.70, 95%CI: 5.47-6.21) or no education (AOR = 1.84, 95%CI: 1.21-3.37), as well as having a husband/partner who sometimes (AOR = 3.37, 95%CI: 1.56-7.30) or often (AOR = 12.87, 95%CI: 5.64-29.38) gets drunk were positively associated with sexual violence. However, women from male-headed households (AOR = 0.52, 95%CI: 0.29-0.92) were less likely to experience sexual violence. Conclusions There is a need to demystify negative culturally-rooted beliefs favouring sexual violence, such as justified beating, as well as increase efforts to promote women's empowerment and healthcare access. Moreover, engaging men in anti-sexual violence strategies is paramount to addressing male-related issues that expose women to sexual violence.